2020
DOI: 10.3390/su12041413
|View full text |Cite
|
Sign up to set email alerts
|

How Are Information Technologies Addressing Broiler Welfare? A Systematic Review Based on the Welfare Quality® Assessment

Abstract: This systematic review aims to explore how information technologies (ITs) are currently used to monitor the welfare of broiler chickens. The question posed for the review was “which ITs are related to welfare and how do they monitor this for broilers?”. The Welfare Quality® (WQ) protocol for broiler assessment was utilized as a framework to analyse suitable articles. A total of 57 studies were reviewed wherein all principles of broiler welfare were addressed. The “good health” principle was the main criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 100 publications
(184 reference statements)
0
10
0
Order By: Relevance
“…Prior to the systematic literature search, an initial non-systematic literature search was performed by two researchers independently. This initial search was inspired by the concept map used by Rios et al, investigating ITs for welfare assessment in broilers [11]. After the initial search, the two researchers created in collaboration the concept map used for the systematic literature search as presented in Table 1.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…Prior to the systematic literature search, an initial non-systematic literature search was performed by two researchers independently. This initial search was inspired by the concept map used by Rios et al, investigating ITs for welfare assessment in broilers [11]. After the initial search, the two researchers created in collaboration the concept map used for the systematic literature search as presented in Table 1.…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…In these systems, birds experience several housing constraints such as high stocking density, poor air quality, and high moisture in the litter, with welfare issues such as leg health disorders (e.g., rickets, dyschondroplasia, lameness, angular bone deformities, hock burns, and foot pad dermatitis) and compromised behavioral repertoire (Dawkins et al, 2004;Bessei, 2006;Angel, 2007;Averós and Estevez, 2018). While free-range housing is used for both fast-and slow-growing broilers, welfare improvements in conventional intensive indoor production systems remains a focus point in broiler welfare research (Bracke et al, 2019;Rios et al, 2020). A range of lighting factors (i.e., source, intensity, photoperiods, and spectrum) have consequences for broiler production, behavior and welfare (Buyse et al, 1996;Olanrewaju et al, 2006;Soliman and El-Sabrout, 2020).…”
Section: Effects Of Uv Light In Meat Chickens (Excluding Breeder Birds)mentioning
confidence: 99%
“…With respect to the sensors used in poultry PLF, they found that cameras were used in a large proportion of the studies (42.42%) while the use of microphones was less popular (14.02%). Another review, comprising 57 studies, found that only 8% used sound technology [40]. Therefore, the general trend in PLF is the capture of a lot of data from different kind of sensors that must be processed with big data and internet of things technologies to facilitate the smart management of poultry [41].…”
Section: Acoustic Analysis Of Bird Vocalisations For Welfare Evaluationmentioning
confidence: 99%